An 18th-century designed landscape: perimeter boundary wall surveys and boundary evaluations (Scottish Historical and Archaeological Internet Reports, 2010)
This chapter is concerned with the boundaries of Dalkeith Park formerly the formal gardens and grounds of the 18th-century Dalkeith House. Survey methodology and results are considered. Within the sections of wall examined by evaluation it was clear that there was uniformity in its design.